Non-inhibited miRNAs shape the cellular response to anti-miR - Androsavich, John R. (Oxford University Press, 2014)
Identification of primary microRNA (miRNA) gene targets is critical for developing miRNA-based therapeutics and understanding their mechanisms of action. However, disentangling primary target derepression induced by miRNA inhibition from secondary effects on the transcriptome remains a technical challenge. Here, we utilized RNA immunoprecipitation (RIP) combined with competitive binding assays to identify novel primary targets of miR-122. These transcripts physically dissociate from AGO2-miRNA complexes when anti-miR is spiked into liver lysates. mRNA target displacement strongly correlated with expression changes in these genes following in vivo anti-miR dosing, suggesting that derepression of these targets directly reflects changes in AGO2 target occupancy. Importantly, using a metric based on weighted miRNA expression, we found that the most responsive mRNA target candidates in both RIP competition assays and expression profiling experiments were those with fewer alternative seed sites for highly expressed non-inhibited miRNAs. These data strongly suggest that miRNA co-regulation modulates the transcriptomic response to anti-miR. We demonstrate the practical utility of this ‘miR-target impact’ model, and encourage its incorporation, together with the RIP competition assay, into existing target prediction and validation pipelines.